Functional analysis of ectodermal β‐catenin during external genitalia formation. (11th March 2013) - Mazahery, Ahmad Reza; Suzuki, Kentaro; Nagafuchi, Akira; Miyajima, Masayasu; Nakagata, Naomi; Orvis, Grant D.; Behringer, Richard R.; Yamada, Gen
Abstract β‐catenin is a molecule belonging to the armadillo family of proteins that is a crucial core‐component of cellular adherens junctions, and a component of the canonical Wnt‐signaling pathway. We attempted to analyze the functional significance of ectodermal‐derived β‐catenin during the development of the mouse genital tubercle, a mammalian anlage of the external genitalia. For this purpose, the conditional loss of function mouse mutant Wnt7a‐Cre;β‐catf/f was utilized. Loss of ectodermal β‐catenin leads to the formation of urethral cleft during preputial uprising. Although expression of E‐cadherin was retained in the genital tubercle ectoderm of mutants, probably through plakoglobin compensatory expression, expression of other crucial adherens junction components such as α‐catenin and F‐actin in the cell‐cell border were distinctly reduced. We also showed that β‐catenin is necessary for the expression of its transcriptional downstream target Lef‐1 which was localized in the basal layer of the preputial ectoderm, excluding the midventral region at E15.5. Such specialized region was observed to possess cytoplasmic β‐catenin expression at this stage. Coincidentally, mitotically active cells were also found in the basal layer of the preputial ectoderm excluding the midventral region. In mutant genital tubercle, cell proliferation in the preputial ectoderm was decreased. Taken together, we suggest that ectodermal β‐catenin is necessary not only to maintain adherens junction integrity, but also to regulate cell proliferation possibly through Lef‐1 functions. Thus, β‐catenin is shown to perform dual functions, initially as an adhesion molecule and later on as a possible transcription factor.